2006
DOI: 10.1590/s0034-89102006000600015
|View full text |Cite
|
Sign up to set email alerts
|

Saúde e capacidade para o trabalho em trabalhadores de área administrativa

Abstract: OBJECTIVE:To identify dimensions of health associated with work ability and to verify whether such relationships are influenced by demographic or occupational characteristics. METHODS:A cross-sectional study was carried out, including 224 employees of an employee health insurance and retirement savings company in the city of São Paulo, Brazil, in 2001. Subjects responded to self-administered questionnaires evaluating demographic and occupational characteristics, job satisfaction, health, and work ability. Asso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
38
1
23

Year Published

2008
2008
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(65 citation statements)
references
References 12 publications
3
38
1
23
Order By: Relevance
“…Decreased WA and poorer health perception occurred among passive workers who did not exercise regularly and reported no leisure activities. Studies conducted in Brazil have also confirmed the association between good health, high WA and good working conditions, both in the administrative sector and among electricians 19,23 .…”
Section: Healthmentioning
confidence: 74%
See 3 more Smart Citations
“…Decreased WA and poorer health perception occurred among passive workers who did not exercise regularly and reported no leisure activities. Studies conducted in Brazil have also confirmed the association between good health, high WA and good working conditions, both in the administrative sector and among electricians 19,23 .…”
Section: Healthmentioning
confidence: 74%
“…National research on this topic began in the late 1990s and, since then, studies have been conducted in several sectors: health 47,48 , transportation 49 , electrical 12 , administrative 19,50 , food and beverage 51 and non-specific industry 21 . Nearly all the Brazilian literature on the subject stems from cross-sectional studies that assessed predictors of WA and used multiple linear regression models or logistic regression for data analysis.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A capacidade para o trabalho tem sido investigada em indivíduos adultos de diferentes profissões, tanto nas funções operacionais que requerem grande esforço físico (WAL-SH et al, 2004;ANDRADE e MONTEIRO, 2007), como em funções predominantemente cognitivas, como nos cargos administrativos (BELLUSCI; FISCHER, 1999;MARTINEZ;LATORRE, 2006 …”
Section: Capacidade Para O Trabalho E íNdice De Capacidade Para O Traunclassified